089. TACE for Residive Malignant Peripheral Nerve Sheath Tumor and Leiomyosarcoma: Case Series - Ferdiansyah, Rheza; Rizki, Kiki Akhmad (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Malignant peripheral nerve sheath tumors (MPNST) are malignant, locally aggressive soft tissue sarcomas (STS) of the peripheral nerve or nerve sheath cells. Leiomyosarcomas are malignant tumors originating from the smooth muscle. Transarterial chemoembolization (TACE) is an interventional treatment to deliver chemoembolic materials. Case : First case is a 50-year-old male visited Oncology Surgery Polyclinic due to the presence of a tumor on his left forearm that was progressively increasing in size during the past two months. The MRI was done, the diagnosis of a residive malignant peripheral nerve sheath tumor was made. Second case is a 40-year-old female visited the Oncology Surgery Polyclinic due to the presence of a tumor on her right breast that was progressively increasing in size and the diagnosis of a Leiomyosarcoma at the right breast was made. Transarterial chemoembolization (TACE) was performed to both of the cases. Conclusion : MPNST and Leiomyosarcoma are malignant tumor that can be treated with doxorubicin chemotherapy through the TACE procedure.